P023 A mixed-methods analysis of a pay-it-forward gonorrhea/chlamydia testing program among men who have sex with men in china. (14th July 2019) - Li, Katherine; Yang, Fan; Huang, Wenting; Zhao, Yang; Wu, Dan; Tang, Weiming; Wu, Feng; Yang, Ligang; Zhang, Tiange; Muessig, Kate; Tucker, Joseph
Abstract : Background: Neisseria gonorrhoeae and Chlamydia trachomatis are common among Chinese men who have sex with men (MSM), but testing rates are low. We developed a pay-it-forward program, where each man receives a free gonorrhea/chlamydia test and can then choose to donate toward testing for future participants. This study aims to investigate the facilitators of increased gonorrhea/chlamydia testing among MSM in the pay-it-forward program. Methods: We collected survey data on socio-demographics and perceived benefits of the pay-it-forward program among men offered the pay-it-forward intervention as part of a quasi-experimental study in Guangzhou, China. We analyzed testing uptake using multivariable logistic regression. We also conducted twelve semi-structured interviews with men who received testing eliciting their perceptions of the program. Interview data were coded to identify themes. Results: 204 MSM were offered pay-it-forward and 109 (54%) received gonorrhea/chlamydia testing. Across survey and interview data, the main facilitators of testing were (1) lower cost and (2) care for MSM community. First, 48/204 (24%) participants selected discounted testing as a benefit of pay-it-forward, and receiving testing was not associated with income. In interviews, the majority of participants felt that standard hospital-based testing was prohibitively expensive, especially for students (150 RMB, ∼USD 21.50); pay-it-forward made testing affordable for them. Second, 141/204 (70%) men selected 'more MSM can get tested' or 'I can help someone else' as benefits of pay-it-forward, and selecting at least one of these options was associated with getting tested (aOR = 2.59, 95% CI = 1.31–5.15). In interviews, some men expressed desire to contribute to the MSM community; others felt that encouraging others to test could also eventually benefit themselves. Conclusion: This pay-it-forward program may increase MSM gonorrhea/chlamydia testing rates by reducing barriers due to cost and mobilizing community altruism. This model may be useful for other settings and sexual health services. Disclosure: No significant relationships.